Micromorphological analysis of spores on various species of pteridophytes: Implications for species identifications - MILDAWATI MILDAWATI; SHAVIRA PERDANI SAFITRIA HANAFI; ELSA PUTRI; M. ABDUL AZIZ; SHERLI IVANI; NURHASNA NURHASNA; SOLFIYENI SOLFIYENI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mildawati, Hanafi SPS, Putri E, Aziz MA, Ivani S, Nurhasna, Solfiyeni. 2025. Micromorphological analysis of spores on various species of pteridophytes: Implications for species identifications. Biodiversitas 26: 2332-2338. Pteridophytes, a group of vascular plants, play a critical role in ecosystem balance. However, taxonomic challenges persist in identifying and classifying their species. Spore micromorphological characters, unique to each species, offer a potential solution to these issues. This study aimed to examine the spore micromorphology of several pteridophyte species growing on the Universitas Andalas campus, Padang, Indonesia. The species examined included Antrophyum callifolium, Asplenium nidus, Davallia denticulata, Pteris vittata, Pyrrosia adnascens, P. longifolia, and P. piloselloides. Spore samples were observed using a binocular light microscope with a magnification 40x objective lens and documented with the OptiLabView4 application. The results revealed that most pteridophytes spores studied exhibited a monolete laesura type with an ellipsoid shape, except for A. callifolium and P. vittata, which showed a trilete laesura type with a tetrahedral shape. Exospore ornamentation was varied: verrucate in A. callifolium, A. nidus, D. denticulata, and P. vittata; reticulate in P. adnascens and P. longifolia; and echinate in P. piloselloides. Spore sizes were categorized as medium (25-50 ?m) for A. callifolium, A. nidus, D. denticulata, and P. vittata.; and large (60 ?m) for P. adnascens, P. longifolia, and P. piloselloides. Spore micromorphology of pteridophytes on the Universitas Andalas campus, revealing significant diversity in size, shape, and ornamentation.